ANALYSIS OF THE FRAMING OF NEWS REPORTING OF THE HONORARY DEGREE TO PRABOWO SUBIANTO ON MEDIA TEMPO.CO AND KOMPAS.COM. - winarno, riga ary (Jurusan Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jenderal Soedirman, 2024)
Tempo.co and Kompas.com, reflects significant differences in news framing. This analysis aims to explore how the two media frame the news and its impact on public perception.Tempo.co focuses on the controversial aspects and criticism surrounding the awarding of the title. This media emphasizes Prabowo's background which is full of issues of human rights violations as well as the potential negative impacts of this decision. Tempo.co uses critical and negative language, focusing attention on existing controversies, including criticism from various public figures and civil society groups. This narrative underscores the negative impact on public trust and moral issues that may arise from degree-granting decisions. On the contrary, Kompas.com emphasizes the positive aspects and achievements of awarding honorary degrees. This media emphasizes the reasons and justifications behind the decision, focusing on Prabowo's contributions and achievements that are considered worthy of appreciation. Kompas.com uses supportive and constructive language, highlighting the benefits and positive impacts of awarding a degree.